(untitled) (The Insight, 2025)
Background: This study aimed to investigate changes in plasma lipid profile as potential predictors of disease severity in dengue infection. Methods & Materials: A prospective observational study was conducted on 120 laboratory-confirmed dengue patients, classified according to the WHO 2009 criteria as dengue without warning signs (n=52), dengue with warning signs (n=46), and severe dengue (n=22). Plasma lipid profile including total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglycerides during admission. Clinical and laboratory parameters were recorded, and their correlation with lipid levels were analyzed. Results: Significantly lower levels of total cholesterol, HDL, and LDL were observed in patients with severe dengue compared to those with milder forms (p<0.001), and in non-survivors (n=6) compared to survivors (n=114) (p<0.001). ROC curve analysis revealed good discriminatory power of total cholesterol (AUC=0.842), HDL (AUC=0.826), and LDL (AUC=0.834) for predicting severe dengue. Cut-off values of total cholesterol ≤3.10 mmol/L, HDL ≤0.75 mmol/L, and LDL ≤1.80 mmol/L demonstrated optimal sensitivity and specificity. Multivariate analysis confirmed these parameters as independent predictors of severe dengue after adjusting for confounders. Significant negative correlations were observed between lipid levels and markers of disease severity, including thrombocytopenia, elevated liver enzymes, and clinical complications. Conclusions: Changes in plasma lipid profile, particularly decreased total cholesterol, HDL, and LDL levels, are significantly associated with severe dengue and adverse clinical outcomes. These parameters show promise as early predictors of disease progression and could be incorporated into existing risk stratification tools to improve the management of dengue patients.